Book review - Fuzziness in Information Systems - How to Deal with Crisp and Fuzzy Data in Selection, Classification, and Summarization. Springer International Publishing Switzerland, 2016, written by Miroslav Hudec - Vujošević, Mirko (Yugoslav Journal of Operations Research; Vol 27 No 1 (2017), 2017)
Fuzziness in Information Systems - How to Deal with Crisp and Fuzzy Data in Selection, Classification, and Summarization. Springer International Publishing Switzerland, 2016, written by Miroslav Hudec